Sistema de despliegue en red de los indicadores de desempeño del robot Delta Summit Handler - Rodríguez-Chaverri, David (Instituto Tecnológico de Costa Rica, 2002)
The Delta Summit Handler, a robot that costs some hundreds of thousand dollars, is used at Componentes Intel of Costa Rica for testing the microprocessors. For improving the machine utilization of the handler a statistic tool was designed and this tool is the scope of this document. The project takes advantage of a database available in every handler to record every error. This data is displaying in a web site, providing an intranet connection plus a reporting tool. The same process without software automation is difficult: is enough for keeping busy 1 employee for more than 9 hours per day. For this reason at this moment there are no reliable indicators of the machine utilization. Enabling the connection of the Handlers has two risks: the exposition to intranet viruses and decreasing the tool performance. We addressed both installing antivirus software, reducing the intranet/internet access to the minimal possible and designing experiments to measure the run rate with and without the antivirus shield. The reporting tool was implemented using a web application based in ActiveX technology that generates all graphs and indicators plus an Ms-Access database remote collecting tool. The last version of the web site displays 7 indicators and 3 graphs for every handler, all of them related with the most frequent interrupts, the interrupts that take more time, mean times between failures and to repair failures. Because this is confidential information, the site is only accessible for Intel Intranet users.
Proyecto de Graduación (Bachillerato en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2002.
Keywords: Sitios web; Bases de datos; Interrupciones; Programación de computadoras; Internet; Usuarios